Zn2+- Controlled Crystallization and Microstructure in K-Li-Mg-B-Si-Al-F Glass. (10th July 2018) - Garai, Mrinmoy; Maurya, Anoop K.; Roy, Shibayan
Abstract Text: The crystallization of (9-X) K2 O-1Li2 O-12MgO-10B2 O3 -40SiO2 -16Al2 O3 -12MgF2 -X PbO/BaO/ZnO (X =0/5) composition (wt.%) were studied by means of dilatometry, DSC, XRD, SEM and microhardness analysis. Density of base K-Li-Mg-B-Si-Al-F glass (2.59 g.cm –3 ) is found to be increased on addition of the network modifier oxides PbO, BaO and ZnO content. Addition of Pb 2+, Ba 2+ and Zn 2+ furthermore increased the glass transition temperature (Tg. ). A characteristic exothermic hump is found to be appeared in DSC thermograph at the temperature range 800-950°C; and that is ascribed to the formation of crystalline phase fluorophlogopite mica, KMg3 (AlSi3 O10 )F2 . Opaque glass-ceramics were prepared from K-Li-Mg-B-Si-Al-F glasses (with and without containing PbO, BaO and ZnO content) by controlled heat-treatment at 1000°C. Interlocked type microstructure combined of flake like fluorophlogopite mica crystals is obtained in ZnO-containing K-Li-Mg-B-Si-Al-F glass-ceramic; and such microstructural pattern is ascribed to cause large thermal-expansion (>11.5×10 -6 /K, 50-800°C).Vickers Microhardness of base glass-ceramic (5.12 GPa) is increased when contains ZnO (5.26 GPa). ZnO-containing boroaluminosilicate glass-ceramic is, hence, considered with potential interest as they can exhibit the microcrack resistivity in high temperature recycling operation (like SOFC).